Life After Surviving Vehicular Accident: A Phenomenological Inquiry - Edmelyn B. Cacayan; Shayne R. Babaran; Romella Mendez Tuppal (Health Notions, 2020)
Worldwide, one of the leading causes of death and injuries are motor vehicle accidents. This study was conducted to explore motor vehicle accident victims’ experiences after vehicular accident in an attempt to further understand the phenomenon. It is important to know the effects of the accident to the life of survivors in order to make a specific intervention to their specific needs. A qualitative phenomenological design is used, using semi-structured, in depth face to face interviews to elicit accounts of vehicular accident survivors. Findings revealed that driving under influence of alcohol, over speeding, slippery road, and first time driving are some of the causes of accident. Five of the respondents had experienced disturbing thoughts, and some of them had dreams of the accident were happening again. Six of the respondents were afraid that it will happen again when something or someone reminded them of the accident or when seeing the place where they experienced the accident. The result of this study will help and assist health professionals in developing a plan of care to victims of vehicular accidents regardless of severity to have psychological assistance to avoid future problems such as recurrent thoughts, sleep disturbances and others. Keyword: vehicular accident; victim